PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Utami, Destriana Wiryakurnia; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of corporate governance mechanisms such as disclosure on corporate governance practice, board of commissioner, managerial ownership, board committees, and auditor quality on financial performance. This study used a population of all listed firm in Indonesia Stock Exchange in 2013. The sampling method in this research is purposive sampling. There are 220 data that included the criteria. Then, there are 27 samples that include outlier should be excluded from samples of observation. So, the final amounts of the sample are 193 data. Multiple regression used to be analysis technique. The empirical result of this study show that disclosure on corporate governance practice has positive effect to ROE significantly. Managerial ownership and board committees have negative effect to ROE significantly. Auditor quality has negative effect to Tobin’s Q significantly.